PENGEMBANGAN DAN INOVASI DESAIN MOTIF DAN TENUN SOCIAL MEDIA MARKETING DALAM RANGKA MENINGKATKAN KOMERSIALISASI USAHA BANUN SONGKET DI KABUPATEN SOLOK - Ratni Prima Lita; Laura Amelia Triani; Rita Rahayu; Eri Besra; Budi Rahmadya; Rida Rahim; Suziana Suziana; Yanti Yanti; Verni Juita; Verinita Verinita; Desyetti Desyetti; Wardah Awwalin Ikhsaniah Saldi; Husnul Khatimah; Yaza Fitria; Bima Satria Wahyudi; Alfin Kurniawan (LPPM Universitas Andalas, 2025)
Banun Songket Enterprise is a Minangkabau weaving business group located in Solok Regency. Despite its strong potential, the enterprise continues to face several obstacles, particularly in terms of limited motif design variations and the relatively low utilization of social media platforms for promotional purposes. This community service program aimed to enhance product competitiveness through the creation of more attractive motifs, the use of digital design to accelerate production, and the optimization of social media marketing to expand market reach beyond the local area. The activities were realized through a combination of intensive training and ongoing business mentoring. Training was conducted over two days, while personalized business consultations were held over six months in six sessions. Outcomes were assessed through three stages: socialization and licensing, implementation (including motif design training, digital design, and social media marketing assistance), and monitoring and evaluation. The program successfully produced three new motifs with more appealing designs and established professional Instagram and TikTok accounts for Banun Songket. Both management and artisans showed high enthusiasm throughout the activities. However, challenges remain in ensuring continuous practice for digital motif design and maintaining consistent social media content due to the artisans’ busy schedules in fulfilling weaving orders. Future programs are expected to continue with support from Universitas Andalas and the Solok Regency Government.